Copy number variations of CBF genes at the Fr‐A2 locus are essential components of winter hardiness in wheat. (8th February 2017) - Würschum, Tobias; Longin, C. Friedrich H.; Hahn, Volker; Tucker, Matthew R.; Leiser, Willmar L.
Summary: Winter hardiness is important for the adaptation of wheat to the harsh winter conditions in temperate regions and is thus also an important breeding goal. Here, we employed a panel of 407 European winter wheat cultivars to dissect the genetic architecture of winter hardiness. We show that copy number variation (CNV) of CBF (C‐repeat Binding Factor) genes at the Fr‐A2 locus is the essential component for winter survival, with CBF‐A14 CNV being the most likely causal polymorphism, accounting for 24.3% of the genotypic variance. Genome‐wide association mapping identified several markers in the Fr‐A2 chromosomal region, which even after accounting for the effects of CBF‐A14 copy number explained approximately 15% of the genotypic variance. This suggests that additional, as yet undiscovered, polymorphisms are present at the Fr‐A2 locus. Furthermore, CNV of Vrn‐A1 explained an additional 3.0% of the genotypic variance. The allele frequencies of all loci associated with winter hardiness were found to show geographic patterns consistent with their role in adaptation. Collectively, our results from the candidate gene analysis, association mapping and genome‐wide prediction show that winter hardiness in wheat is a quantitative trait, but with a major contribution of the Fr‐A2 locus. Significance statement: Copy number variation (CNV) in the human genome has been associated with diseases, but little is known about CNV in crops. Here, we used a panel of over 400 winter wheat cultivars to dissect the genetic architecture of winter hardiness. We show that CNV at the Fr‐A2 locus, which is composed of a cluster of CBF genes that are upregulated in response to low temperatures, contributes substantially to winter hardiness in wheat. The allele frequencies of all loci associated with winter hardiness showed geographic patterns consistent with their role in adaptation.